Pengaruh Pemberian Musik Klasik Mozart Terhadap Waktu Pulih Sadar Pasien Kanker Payudara Dengan Anestesi General Di Rsud Dr. Moewardi Surakarta - NURZALLAH, AZHAR PUTRIAYU, Arina Maliya, S.Kep., Msi.Med, Kartinah A.Kep., S.Kep (2015)
Everyone had a different physiological effects in surgery depending on patients general condition, type and nature of the surgary performed, anesthesia technique used, type and dose of medicine gived. All of, it influencial of recovered time conscious cancer mamaepatient after surgery. As a nurse, we can provided complementay therapies by used mozart classical music therapy as on of environment modification and change the mood of patient so that patient can be calm and relax condition. The aim of this study was to explain the effect of mozart classical music therapy on recovered time conscious in cancer mamae with general anesthesia patients Dr.Moewardi hospital at Surakarta. This study was quasi eksperiment with nonequivalent control group design. Samples were 15 respondent contro groug and 15 respondent treatment group (with mozart classical music therapy) cancer mamae with general anesthesia patients with accidental sampling technique. Samples were provide mozart classical music therapy: Eine kleine nachmusic -serenade no.13 in G major for 15 minutes after that it's measure recovered time conscious by aldrete score. The result were analyze by independent sample t-test. The result of statistical had significant value (p value) 0,002 ( p < 0,005) so there was the effect of mozart classical music therapy on recovered time conscious in cancer mamae with general anesthesia patients Dr. Moewardi hospital at Surakarta. The average recovered time conscious cancer mamae in traetment group was 5, 33 minutes and avarage recovered time conscious cancer mamaein control group was 6, 42 minutes. The conclusion of this study that mozart classical music therapy was effective of revovered time conscious in cancer mamae with general anesthesia patient Dr. Moewardi hospital at Surakarta.